Perancangan Layanan Mobile Bengkel Online Menggunakan Metode Location Based Service - Heri; Phie Chyan (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2017)
This research focuses on the utilization of Location Based Service services to find the location of the nearest workshop in Makassar. Workshop is a place to fix two-wheeled vehicles and four-wheeled and more. When damage occurs at the time of use, the vehicle owner is generally confused to find the nearest workshop. In addition, the nearest workshop may not necessarily have a good reputation so that vehicle owners prefer to enter the vehicle in the official workshop. The purpose of this research is to design an information service for customers to find the nearest service based on Location Based Service, so that later both general workshop and authorized workshops can compete to provide good service for customers. Location base service is a Service using Google's global positioning service (GPS) and cell-based location technology. In addition, the LBS consists of several components, namely mobile devices, communication networks, position components, and service and content providers. The research method uses a waterfall method consisting of the stage of analysis, design, design and implementation. The results of this study is an application that can receive requests for repair or service periodically by the owner of the vehicle to the workshop. When the repair shop receives requests for repair or maintenance, the workshop will pick up the vehicle.